Role of pyruvate dehydrogenase inhibition in the development of hypertrophy in the hyperthyroid rat heart: a combined magnetic resonance imaging and hyperpolarized magnetic resonance spectroscopy study. - Atherton, H; Dodd, M; Heather, L; Schroeder, M; Griffin, J; Radda, G; Clarke, K; Tyler, D (2011)
BACKGROUND: Hyperthyroidism increases heart rate, contractility, cardiac output, and metabolic rate. It is also accompanied by alterations in the regulation of cardiac substrate use. Specifically, hyperthyroidism increases the ex vivo activity of pyruvate dehydrogenase kinase, thereby inhibiting glucose oxidation via pyruvate dehydrogenase. Cardiac hypertrophy is another effect of hyperthyroidism, with an increase in the abundance of mitochondria. Although the hypertrophy is initially beneficial, it can eventually lead to heart failure. The aim of this study was to use hyperpolarized magnetic resonance spectroscopy to investigate the rate and regulation of in vivo pyruvate dehydrogenase flux in the hyperthyroid heart and to establish whether modulation of flux through pyruvate dehydrogenase would alter cardiac hypertrophy. METHODS AND RESULTS: Hyperthyroidism was induced in 18 male Wistar rats with 7 daily intraperitoneal injections of freshly prepared triiodothyronine (0.2 mg x kg(-1) x d(-1)). In vivo pyruvate dehydrogenase flux, assessed with hyperpolarized magnetic resonance spectroscopy, was reduced by 59% in hyperthyroid animals (0.0022 ± 0.0002 versus 0.0055 ± 0.0005 second(-1); P=0.0003), and this reduction was completely reversed by both short- and long-term delivery of dichloroacetic acid, a pyruvate dehydrogenase kinase inhibitor. Hyperpolarized [2-(13)C]pyruvate was also used to evaluate Krebs cycle metabolism and demonstrated a unique marker of anaplerosis, the level of which was significantly increased in the hyperthyroid heart. Cine magnetic resonance imaging showed that long-term dichloroacetic acid treatment significantly reduced the hypertrophy observed in hyperthyroid animals (100 ± 20 versus 200 ± 30 mg; P=0.04) despite no change in the increase observed in cardiac output. CONCLUSIONS: This work has demonstrated that inhibition of glucose oxidation in the hyperthyroid heart in vivo is mediated by pyruvate dehydrogenase kinase. Relieving this inhibition can increase the metabolic flexibility of the hyperthyroid heart and reduce the level of hypertrophy that develops while maintaining the increased cardiac output required to meet the higher systemic metabolic demand.